STUDI PEMIKIRAN ABU ALI AL-FARISI TENTANG GRAMMATIKA ARAB (REPRESENTASI TOKOH NAHWU MADRASAH BAGHDAD) - Ahmad Sirfi Fatoni (Tamaddun: Jurnal Kebudayaan dan Sastra Islam, 2019)
Introduction The nahwu science is a very urgent science in the context to understand about the Arabic texts both classical or modern texts. The conversation related to this science could not be released just like that with the figures of nahwu who played an important role in it. This article will examine Abu Ali al-Farisi’s thought about the development of nahwu as a representative figure from Baghdad’s madrasah. This article also investigates Abu Ali’s partiality to Bashra’s nahwu experts on one hand, while Kuffa’s experts formulation of nahwu on another. In addition, this article also inspects the method that used by Baghdad’s nahwu experts and his characteristic. Data Collection Method The data collection method used is the refer’s method with the noted technique. Analysis Data This article is a qualitative research, the presentation of the analysis is descriptive and critical. Results and Discussions One of Abu Ali’s thoughts is the origin of language is tauqifi’, he also argues that adawatu al-nida are isim fi’il which act on munada, similar to maf’ul bih. As for the partiality of Abu Ali’s nahwu theory which chooses Bashra’s opinion is related to huruf kaanna that sometimes comes as zaidah. In this case, Abu Ali follows the opinion of Khalil and Sibawaih. While the partiality of Abu Ali which chooses Kuffa’s opinion, it comes when he argues that the application of first fi’il in tanazu’ chapter. Conclusion In the general, it can be concluded that the method of Baghdad’s madrasah is ecletic method. This method can be classified into three patterns: Qiyas, Sima’, and Ta’lil. As for the characteristic of Baghdad’s madrasah pattern are: inclusive, flexible, taqlid and logical. Keywords: Ecletic Method, Baghdad Nahwu, Abu Ali’s thought. Keywords: Ecletic Method, Baghdad Nahwu, Abu Ali’s thought.